Reproductive outcomes of female patients with congenital adrenal hyperplasia due to 21-hydroxylase defi ciency - Mouna Feki Mnif; Mahdi Kamoun; Faten Hadj Kacem; Fatma Mnif; Nadia Charfi; Basma Ben Naceur; Nabila Rekik; Mohamed Abid (Indian Journal of Endocrinology and Metabolism, 2013)
Fertility in women with congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21-OHD) appears to be reduced, especially in women with the classic salt-wasting type. Several factors have been suggested to contribute to this subfertility such as androgen excess, adrenal progesterone hypersecretion, consequences of genital reconstructive surgery, secondary polycystic ovaries syndrome, and psychosexual factors. In contrast to this subfertility, pregnancies are commonly normal and uneventful. Adequate glucocorticoid therapy and improvement of surgical and psychological management could contribute to optimize fertility in CAH female patients, even among women with the classic variant. This review provides current information regarding the reproductive outcomes of women with CAH due to 21-OHD and the fertility and pregnancy issues in this population.